The Importance of Archaeological Sites in the Hiuka Karst Lake Area, Routa, Southeast Sulawesi - Sandy Suseno; Melanie Lapenant; Evrard Wadenbaum; Salniwati Salniwati; Dodi Satriadi; Wa Ode Sifatu; Danial Danial (Journal of Law, Social Science and Management, 2026)
Background: The Hiuka Karst Lake area is rich in cultural heritage, including caves containing archaeological remains. Currently, this area is quite isolated but faces a very high level of threat due to destructive exploitation, including mining. Therefore, scientific arguments are needed to serve as a bargaining chip to preserve this area and prevent it from destructive exploitation. Therefore, it is necessary to examine its significance in accordance with Law No. 11 of 2010 concerning Cultural Heritage, thus making the existence of archaeological sites a key bargaining chip. Objective: This research examines archaeological data from cave sites containing archaeological remains in the form of various pottery, porcelain, stone artifacts, metal artifacts, and ecofacts. Methods: This research was conducted through direct exploration in the Hiuka Karst Lake area. Exploration data, including site location, variety of findings, and environmental context, were processed using a Geographic Information System approach to produce distribution maps and data tabulation. The GIS data processing results were then analyzed to formulate conclusions about the significance of the archaeological sites in the area. Results: The Hiuka Karst Lake area contains 20 archaeological caves containing pottery, stone artifacts, metal artifacts, porcelain, and ecofacts. The Hiuka Karst Lake area has historical, scientific, educational, and cultural significance, as stipulated in Law No. 11 of 2010 concerning Cultural Heritage. Conclusion: The Hiuka Karst Lake area is evidence of the development of early civilization in South Sulawesi, a key component in shaping the cultural identity of traditional communities in Southeast Sulawesi, and a space for developing scientific learning practices.  Keywords: Hiuka Karst Lake, Archaeological Remains, Significance, Cave Distribution